Vietnamese-English Bilingualism : Patterns of Code-Switching. - Tuc, Ho-Dac (Routledge Studies in Asian Linguistics., 2014)
This book is concerned with three central issues: the universality of constraints on code-switching, the nature of the relation between language contact and bilingualism, and the social and linguistic components that facilitate code-switching.